Silicon-carbon composite fiber

By using silicon carbon composite fibers in lithium ion batteries to form a SI-C network structure, the battery structure destruction and capacity loss caused by the expansion of silicon anode materials are solved, and higher cycling Kulun efficiency and capacity retention are achieved.

CN119365995APending Publication Date: 2025-01-24UNIFRAX I LLC
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380041778.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-03-21
Filing Date
2023-03-21
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

When silicon is used as anode material in lithium-ion batteries, the internal battery structure is damaged and the capacity is rapidly lost due to the expansion of silicon by 350% during lithiation.

Method used

The silicon carbon composite fiber is adopted, and the Si-C network structure that is tangled is formed by infiltrating the silicon in the carbon structure or the carbon in the silicon structure to improve the cyclic Klun efficiency and capacity retention of the battery.

Benefits of technology

By forming the SI-C composite fiber, the first cycle of lithium-ion batteries of lithium-ion batteries has significantly improved the capacity and cyclic Kulun efficiency of the lithium battery, reducing the damage and capacity loss of the battery structure.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119365995A_ABST
    Figure CN119365995A_ABST
Patent Text Reader

Abstract

A composite fiber includes a porous silicon phase including elemental silicon and a porous carbon phase including elemental carbon. The silicon phase and the carbon phase form an entangled network structure in the composite fiber such that each of the silicon phase and the carbon phase is interconnected and continuous throughout the composite fiber. The silicon phase and the carbon phase together constitute at least 50% by weight of the composite fiber.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS

[0002] This application claims the benefit of U.S. Provisional Patent Application No. 63 / 269,652, filed on March 21, 2022, which is incorporated herein by reference in its entirety.

[0003] Public Domain

[0004] The present disclosure relates to silicon-carbon composite fibers and methods of making and using the same. Background Art

[0005] Lithium-ion batteries have proliferated over the past decade and are now the power source of choice for providing portable power to electronic devices, cordless equipment, and vehicles. As technology has become increasingly dependent on lithium-ion battery power, the lithium-ion battery industry has worked to expand the performance of its batteries to provide maximum versatility to the end user.

[0006] Graphite is commonly used in lithium-ion batteries due to its ability to remain stable and perform its functions over hundreds of cycles with little to no capacity loss. Silicon shows great promise as an anode material due to its extremely high capacity (4000 mAh / g) relative to graphite (372 mAh / g), which is the current industry standard. However, silicon has a limitation of expanding 350% upon lithiation. This expansion can cause severe damage to the internal cell structure and lead to rapid loss of capacity as the cell components are damaged and the anode grinds itself into smaller pieces and eventually loses electrical connections. Therefore, there is a continuing need for improved silicon-containing anode materials and methods of making such silicon-containing anode materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0007] Various embodiments of the present disclosure will be more fully understood from the detailed description and drawings given below. In the drawings, the same reference numerals may indicate the same or functionally similar elements. The embodiments are described in detail below with reference to the drawings, in which:

[0008] Figure 1 is a graph summarizing the results from Example 1.

[0009] Figure 2 is a graph summarizing the results from Example 1.

[0010] Figure 3 is a graph summarizing the results from Example 2.

[0011] Details

[0012] The following disclosure provides many different embodiments or examples. Specific examples of components and arrangements are described below to simplify the disclosure. Of course, these are merely examples and are not intended to be limiting. In addition, the disclosure may repeat reference numerals and / or letters in various examples. This repetition is for simplicity and clarity purposes, and does not in itself represent the relationship between the various embodiments and / or configurations discussed.

[0013] Composite Fiber

[0014] The present disclosure provides a silicon-carbon composite fiber, which includes a silicon phase ("Si phase") and a carbon phase ("C phase"). The Si phase and the C phase form an entangled network structure in the fiber, wherein each of the phases is interconnected and continuous throughout the fiber. The Si phase includes nanocrystalline or amorphous elemental silicon. The Si phase is present in the fiber in a range of greater than 0 wt % to less than 100 wt %. The C phase includes amorphous or crystalline carbon and is present in the fiber in a range of greater than 0 wt % to less than 100 wt %. In some embodiments, the sum of the Si phase and the C phase is between 50 wt % and 100 wt %. In some embodiments, the C phase accounts for at least 30 wt % of the fiber and / or the Si phase accounts for at least 20 wt % of the fiber.

[0015] In one or more embodiments, the composite fibers may also contain amorphous or crystalline silicon oxide SiO x (x≤2). The composite material may also contain other impurities, such as aluminum (Al), magnesium (Mg), chlorine (Cl), sodium (Na), nitrogen (N), carbon oxides (CO x )(x≤2) and / or hydrocarbon chains. In some embodiments, the composite fibers contain 5 wt % or less, 4 wt % or less, 3 wt % or less, 2 wt % or less, or 1 wt % or less of Al. In some embodiments, the composite fibers contain 5 wt % or less, 4 wt % or less, 3 wt % or less, 2 wt % or less, or 1 wt % or less of Mg. In some embodiments, the composite fibers contain 40 wt % or less, 35 wt % or less, 30 wt % or less, 25 wt % or less, 20 wt % or less, 15 wt % or less, 10 wt % or less, or 5 wt % or less of amorphous or crystalline silicon oxide SiO x (x≤2).

[0016] In one or more embodiments, the composite fibers of the present disclosure have a diameter greater than 0 to 100 m 2 / g, 0.1 to 45m 2 / g, 0.1 to 10m 2 / g, or 0.1 to 6m 2 / g of BET specific surface area ("SSA").

[0017] In one or more embodiments, the composite fibers have a thickness of greater than 0 to 0.3 cm 3 / g, 0.01 to 0.3 cm 3 / g, greater than 0 to 0.05cm 3 / g, 0.01 to 0.03 cm 3 / g, greater than 0 to 0.1cm 3 / g, 0.02 to 0.06 cm 3 / g, or 0.05 to 0.25 cm 3 / g pore volume.

[0018] In one or more embodiments, the composite fibers have an average pore size of 5 to 80 nm, 15 to 55 nm, 20 to 35 nm, or 15 to 40 nm.

[0019] In one or more embodiments, the composite fibers have an average diameter of 0.1 to 20 microns, 0.1 to 10 microns, 0.5 to 6 microns, 1 to 8 microns, or 2 to 5 microns.

[0020] In one or more embodiments, the composite fibers have an aspect ratio of fiber length to diameter of at least 3, at least 5, or at least 10.

[0021] The nanocrystalline silicon (elemental silicon) of Si phase can have crystallites, and the crystallites have an average size of 10 to 100nm, 15 to 50nm, 20 to 45nm, 20 to 50nm or 20 to 40nm. In some embodiments, the Si phase comprises at least 50 weight %, at least 60 weight %, at least 70 weight %, at least 75 weight %, at least 80 weight %, 75 to 90 weight % or at least 90 weight % of nanocrystalline silicon based on the gross weight of the Si phase. In some embodiments, the Si phase comprises at most 50 weight %, at most 40 weight %, at most 30 weight %, at most 20 weight % or at most 10 weight % of amorphous or crystalline silicon oxide (SiO x (x≤2)). In some embodiments, the Si phase consists of nanocrystalline silicon, amorphous silicon, and amorphous or crystalline silicon oxide.

[0022] In some embodiments, the Si phase is composed of amorphous and crystalline silicon or is composed of crystalline silicon. In such an embodiment, there may be a silica phase, wherein the silica phase is composed of amorphous and / or crystalline silicon oxide. The silica phase may be continuous or discontinuous in the composite fiber. For example, the silica phase may form an island in the Si phase and / or the C phase. In some embodiments, the weight ratio between the Si phase and the silica phase in the composite fiber is 1:1 to 30:1, 1:1 to 20:1, 2:1 to 10:1 or 5:1 to 10:1. In some embodiments, the silica phase is mainly amorphous silica, and the weight ratio of amorphous silica to crystalline silica is greater than 1:1 to 500:1, 2:1 to 200:1, 10:1 to 100:1 or 50:1 to 100:1.

[0023] Crystalline silicon is formed from silicon crystallites. Without being bound by theory, it is believed that a silicon crystallite size of at least 10 nm increases the first cycle coulombic efficiency (FCE) of a half-cell comprising the composite fiber. FCE measures the amount of capacity that is irreversibly lost during the first cycle of the battery pack. Minimizing this loss is important because the lost capacity (i.e., the used lithium ions) is carried in the battery pack as dead weight over the life of the battery pack. It is believed that this loss is primarily caused by the formation of a solid electrolyte interface (SEI) on the surface of the active material, which traps lithium inside the silicon particles. By increasing the size of the silicon crystallites, the portion of lithium ions consumed during the formation of the SEI on the surface of the silicon crystallites is less because the specific surface area of ​​the material decreases as the crystallite size increases.

[0024] The C phase can have a size of carbon crystallites in the range of 1 to 100nm, 15 to 50nm, 1 to 50nm or 5 to 20nm. In some embodiments, the C phase comprises at least 50% by weight, at least 60% by weight, at least 70% by weight or at least 80% by weight of crystalline carbon based on the total weight of the C phase. In other embodiments, the C phase comprises at most 50% by weight, at most 40% by weight, at most 30% by weight, at most 20% by weight or at most 10% by weight of crystalline carbon. In some embodiments, the C phase comprises at most 50% by weight, at most 40% by weight, at most 30% by weight, at most 20% by weight or at most 10% by weight of amorphous carbon. In other embodiments, the C phase comprises at least 50% by weight, at least 60% by weight, at least 70% by weight or at least 80% by weight of amorphous carbon. In some embodiments, the C phase is composed of crystalline carbon and amorphous carbon.

[0025] In one or more embodiments, one of the Si phase or the C phase has a crystalline content greater than 50 wt % and the other of the Si phase or the C phase has a crystalline content less than 50 wt % based on the weight of each phase. In some embodiments, one of the Si phase or the C phase has a crystalline content greater than 60 wt % and the other of the Si phase or the C phase has a crystalline content less than 40 wt %. In some embodiments, one of the Si phase or the C phase has a crystalline content greater than 70 wt % and the other of the Si phase or the C phase has a crystalline content less than 30 wt %.

[0026] Carbon Precursor Fiber

[0027] In some embodiments, the composite fiber is formed by infiltrating a carbon structure with silicon. For example, the composite fiber can be formed by first making a porous carbon fiber and then infiltrating silicon into the pore structure. Silicon infiltration can be performed by chemical vapor deposition (CVD) using silicon precursor gases such as silane or trichlorosilane. The manufacture of porous carbon fibers can include multiple steps. For example, synthetic polymer fibers can be first made using polymers such as polyacrylonitrile (PAN), asphalt, rayon, and resin. Carbon fibers can then be made by pyrolysis of the synthetic polymer. In order to make the carbon fiber porous, the carbon fiber can be treated by activation or chemical stripping. In the activation method, the porous structure of the carbon fiber is formed by heat treating the carbon fiber (e.g., at 700°C to 1000°C) in an oxidizing atmosphere. In the chemical stripping method, the carbon fiber can be treated with a stripping agent (e.g., acid), and an electric charge can be applied to the fiber. Alternatively, a polymer blend, such as PAN mixed with polymethyl methacrylate (PMMA), can be fiberized into a polymer fiber, which is then oxidized and phase separated. PMMA can then be removed by pyrolysis, leaving a porous carbon fiber.

[0028] In some embodiments, prior to infiltration with silicon, the porous carbon fibers contain at least 50 wt%, at least 60 wt%, at least 70 wt%, or at least 80 wt% crystalline carbon. The porous carbon fibers may contain up to 50 wt%, up to 40 wt%, up to 30 wt%, up to 20 wt%, or up to 10 wt% amorphous carbon. The porous carbon fibers may contain up to 15 wt%, up to 10 wt%, or up to 5 wt% impurities (components other than crystalline or amorphous carbon).

[0029] Porous Silica Fiber Template (PSFT)

[0030] In some embodiments, the composite fiber is formed by infiltrating a silicon structure with carbon. For example, the composite fiber can be formed by first making a porous silicon fiber template (PSFT) containing metallic silicon and then infiltrating carbon into the pores. To make the PSFT, a fiber containing SiO2, i.e., a precursor fiber, is first made. The precursor fiber can be a silica fiber made by a sol-gel fiberization process or by acid leaching oxide glass fibers.

[0031] The precursor fibers are reduced to PSFT containing metallic silicon by, for example, magnesium thermal reduction. The PSFT is then infiltrated with carbon, for example by chemical vapor deposition (CVD) from a carbonaceous source (e.g., acetylene), or using other deposition methods such as physical vapor deposition, sputtering, atomic layer deposition, or by first infiltrating the porous fibers with a hydrocarbon polymer (e.g., a resin, polyvinyl acetate (PVA)) and converting the polymer to carbon by pyrolysis.

[0032] In one or more embodiments, the size of silicon crystallites within the PSFT can be controlled by the magnesium thermal reduction conditions. In particular, it has been found that larger temperature increases and / or longer exposure to such temperatures tend to form larger silicon crystallites. The thermal effect ΔT is characterized by the calculated temperature increase (i.e., an increase above the firing temperature used to initiate the reaction, such as about 550 to 600° C.) from the exothermic magnesium thermal reduction reaction. The magnesium thermal reduction reaction is as follows:

[0033] 1SiO2+2Mg→2MgO+1Si

[0034] The maximum temperature increase (ΔT) from this reaction can be estimated by the following formula:

[0035]

[0036] Where ΔH is the enthalpy of reaction per mole, M Mg is the molar mass of Mg, m Mg 、m Si 、m MgO , M mod are the masses of Mg, Si, MgO and moderator, respectively, and C p,Si , C p,MgO , C p,mod are the specific heat capacities of Si, MgO and moderator respectively.

[0037] In some embodiments, ΔT can be maintained at about 300°C to about 900°C or about 300°C to about 700°C. ΔT can be controlled by, for example, varying the amount of moderator used in the reaction. Typically, increasing the amount of moderator will reduce ΔT because the moderator constitutes a thermal mass that will absorb the heat of reaction. Moderators may include, but are not limited to, sodium chloride, aluminum oxide, aluminum silicate (alumina silicate), zirconium oxide, zirconium silicate (zirconia silicate), magnesium oxide, carbon, silicon carbide, silicon nitride, or any material having a melting point of at least 800°C. The exposure time of PSFT to ΔT can be very fast (e.g., almost spontaneous). In some embodiments, an insulating crucible such as an alumina crucible can extend the effect of ΔT so that larger crystallites can be formed at relatively low ΔT (e.g., from about 200°C to about 600°C).

[0038] High ΔT or long exposure to it can result in many by-products, such as forsterite, ringwoodite, crystalline silica, spinel, enstatite, and / or pyroxene. In some embodiments, the PSFT may be subjected to washing, such as acid washing, to remove one or more of these by-products. In some embodiments, the PSFT - before or after washing - may include up to 10 wt%, up to 5 wt%, up to 3 wt%, up to 2 wt%, or up to 1 wt% of total by-products. In some embodiments, forsterite is present in the washed or unwashed PSFT in an amount of up to 5 wt%, up to 3 wt%, up to 2 wt%, less than 2 wt%, or less than 1 wt%. In some embodiments, ringwoodite is present in the washed or unwashed PSFT in an amount of up to 3 wt%, up to 2 wt%, less than 2 wt%, or less than 1 wt%. In some embodiments, enstatite is present in the washed or unwashed PSFT in an amount of up to 3 wt%, up to 2 wt%, less than 2 wt%, less than 1 wt%, or less than 0.5 wt%. In some embodiments, spinel is present in the washed or unwashed PSFT in an amount of up to 3 wt%, up to 2 wt%, less than 2 wt%, less than 1 wt%, or less than 0.5 wt%. In some embodiments, crystalline silica is present in the washed or unwashed PSFT in an amount of up to 3 wt%, up to 2 wt%, less than 2 wt%, less than 1 wt%, or less than 0.5 wt%. In some embodiments, pyroxene is present in the washed or unwashed PSFT in an amount of up to 3 wt%, up to 2 wt%, less than 2 wt%, less than 1 wt%, or less than 0.5 wt%. In some embodiments, ΔT is kept below 700°C, below 600°C, or below 500°C to minimize the formation of such by-products.

[0039] In some embodiments, the maximum reaction temperature observed during the magnesium thermal reduction of the silica fibers (typically, for a fraction of a second) is 1500° C., 1400° C., 1300° C., 1200° C., 1100° C., 1000° C., 900° C., 800° C., 700° C., or 600° C. In some embodiments, the maximum reaction temperature is at least 300° C., 400° C., 500° C., 600° C., 700° C., 800° C., 900° C., 1000° C., 1100° C., 1200° C., 1300° C., or 1400° C. In some embodiments, the maximum reaction temperature can be between any logical combination of the foregoing upper and lower limits.

[0040] PSFT containing metallic silicon acts as a template matrix for incorporation of carbon to form composite fibers. The metallic silicon-containing fibers may also have an average pore size of 5 to 80 nm, 0.2 to 0.9 cm 3 / g pore volume, and 50 to 350m 2 The PSFT may have a crystalline silicon content (Si%) of 50-100 wt%, at least 75 wt%, 75 to 90 wt%, or at least 90 wt%, and a silicon crystallite size of 10 to 100 nm, 15 to 50 nm, 20 to 50 nm, 20 to 45 nm, or 20 to 40 nm.

[0041] In some embodiments, the PSFT comprises 50 to 100 weight percent crystalline silicon and 0 to 50 weight percent amorphous silicon oxide (SiO x ). The amorphous silicon oxide in PSFT is either stoichiometric (SiO2) or non-stoichiometric SiO x , where x < 2. In some embodiments, prior to infiltration with carbon, the PSFT comprises at least 50 wt%, at least 60 wt%, at least 70 wt%, at least 75 wt%, 75 to 90 wt%, at least 80 wt%, or at least 90 wt% crystalline silicon (nanocrystalline silicon). The PSFT may comprise up to 50 wt%, up to 40 wt%, up to 30 wt%, up to 20 wt%, or up to 10 wt% amorphous or crystalline silicon oxide. The PSFT may comprise up to 15 wt%, up to 10 wt%, or up to 5 wt% impurities (components other than silicon or silicon oxide).

[0042] Examples of material properties of PSFT are summarized in Table 1 below. Material properties can be controlled by reduction recipe design, firing temperature program, post-heat treatment, load ratio and / or the particle size of the moderator. For example, changing the particle size of the moderator will change the packing density of the batch or the spatial allocation among the reactants. For larger moderator particles, the crystallite size tends to be larger. In some embodiments, a larger crystallite size can be achieved by a two-step firing method, wherein the first firing is carried out in the presence of a moderator to achieve a crystallite size of about 6 to 12 nm, and the second firing increases the crystallite size to about 20 to 100 nm in the presence of a reduced amount of moderator (or no moderator). Between the first and second firings, the fired batch is sieved to remove the moderator from the first roasting and / or washed to remove magnesium oxide (MgO). With regard to the load ratio, a higher load relative to the size of a heating vessel (e.g., a crucible, a conveyor belt, or a rotary kiln) generally results in a larger crystallite size because the heating vessel acts as a moderator. That is, in a continuous process, a higher feed rate on a conveyor belt can result in a larger crystallite size, and in a batch process, a higher loading within the batch can result in a larger crystallite size. In some embodiments, the weight ratio of moderator (e.g., sodium chloride and / or alumina) to magnesium is at most 15, at most 12, at most 10, or at most 7.

[0043] Table 1: Material properties of Si fiber templates

[0044] Si fiber template properties scope Si weight% 75-90 or at least 90 Si size (nm) 10-100 or 15-50 <![CDATA[SSA(m 2 / g)]]> 50-350 or 80-200 Pore ​​size (nm) 5-80 <![CDATA[Pore volume (cm 3 / g)]]> 0.2-0.9

[0045] In one or more embodiments, to form the composite fibers, the PSFT is infiltrated with carbon. In such embodiments, the Si-C composite fibers may have a carbon content of 20 to 70 wt%, 20 to 45 wt%, 32 to 50 wt%, or 30 to 50 wt%, having a FCE of at least 78% in a half-cell test and a first cycle specific delithiation capacity (1 SDC) of at least 1300 mAh / g or at least 1800 mAh / g.

[0046] In one or more embodiments, the majority elements in the composite fiber are Si, C, and oxygen (O), wherein these elements comprise, for example, at least 50 wt%, at least 60 wt%, at least 70 wt%, at least 80 wt%, at least 90 wt%, at least 95 wt%, at least 99 wt%, or at least 99.5 wt% of the composite fiber.

[0047] In some embodiments, the composite fiber has a value of at least 77, at least 78, at least 79, or at least 80 of Formula 1 below, wherein X is the average silicon crystallite size in the Si phase in nm, and Y is the weight percent of the C phase based on the total weight of the composite fiber:

[0048] 85.634*X / (X+0.0824*(62.79-Y)) Formula 1

[0049] In some embodiments, the composite fiber has a value of at least 1200, at least 1300, at least 1400, at least 1500, at least 1800, or at least 2000 of Formula 2, wherein Y is the weight percent of the C phase based on the total weight of the composite fiber, and Z is the weight percent of elemental silicon in the Si phase:

[0050] 31.486*(100-Y)*Z / 100 Formula 2

[0051] In some embodiments, the composite fiber comprises a Si phase and a C phase, the Si phase having at least 90 wt% crystalline silicon having an average crystallite size of 20 to 40 nm, and the C phase accounting for 20 to 45 wt% of the composite fiber. An anode including the composite fiber may be capable of providing a 1 SDC greater than 1800 mAh / g and a FCE greater than 78%.

[0052] In some embodiments, the composite fiber comprises a Si phase and a C phase, the Si phase having 75-90 wt % crystalline silicon, the crystalline silicon having an average crystallite size of 20 to 45 nm, and the C phase accounting for 32 to 50 wt % of the composite fiber. An anode including the composite fiber may be capable of providing a 1 SDC greater than 1300 mAh / g, a FCE greater than 78%, and a tenth cycle coulombic efficiency (10CE) greater than 98.7%.

[0053] According to embodiments of the present disclosure, FCE is improved by forming composite fibers of entangled Si-C domains. It can be expected that in the case of 100% carbon, the specific capacity is reduced to a minimum (about 372 mAh / g if the carbon is pure graphite, and even lower if the carbon is carbon black). Therefore, it is important to balance FCE and capacity by appropriately adjusting the penetration of carbon, especially in full cell or battery design.

[0054] The amount of carbon that can penetrate into the PSFT is generally limited by the pore volume of the PSFT, i.e. the void space accessible to the carbon. A higher pore volume allows more carbon to penetrate, thus resulting in a higher possible carbon content.

[0055] Due to the infiltration of carbon or silicon into PSFT or carbon fibers, the total volume of the formed Si-C composite material is unchanged relative to the original PSFT or carbon fiber template. However, the FCE is significantly improved, and the charge and discharge volumetric capacity of a single fiber is increased. Therefore, the composite Si-C fibers can provide superior properties compared to simple mixtures of Si fibers and carbon materials (e.g., carbon black or graphite).

[0056] Without being bound by theory, it is believed that this is at least in part due to the improved transport and diffusion rates of electrons and lithium ions due to the interconnected carbon network in the fiber. Electrons and lithium ions have a higher diffusion rate in carbon than silicon. The interconnected carbon network in the composite fiber promotes the transport of electrons and lithium ions from the outer surface of the composite fiber to the interior of the composite fiber or from the interior of the composite fiber to the outer surface of the composite fiber. Therefore, the number of electrons and lithium ions and their transport rates increase with the increase of carbon content in the fiber.

[0057] The improvement in diffusion rate also reduces the exposure time of tensile stress accumulation on the Si domain surface during the delithiation step, which helps avoid cracking of the silicon domain. The improvement in diffusion rate also helps reduce the exposure time of tensile stress accumulation on the fiber surface during the delithiation step, and thus avoids cracking of the fiber surface.

[0058] In some embodiments, the composite fiber may include lithium, wherein the lithium and at least a portion of the silicon from the Si phase form a Li x Si alloy, wherein x is greater than 0 to 4. In some embodiments, the lithium-containing composite fiber further comprises Li2SiO3. In some embodiments, the lithium-containing composite fiber can be formed by making a nanoporous fiber structure of one of silicon or carbon, then infiltrating the structure with the other of carbon or silicon, and then reacting the infiltrated structure with a lithium source to form Li x In other embodiments, the lithium-containing composite fiber can be formed by making a nanoporous fiber structure of silicon and then reacting the structure with a lithium source to form Li x Si alloy, and finally infiltrating the structure with carbon. In other embodiments, lithium-containing composite materials can be formed by introducing lithium into Si-C composite fibers to form Li x Si alloy. Example

[0059] Example 1

[0060] Batches of PSFT were formed using magnesium thermal reduction under different conditions, and each of the batches was subsequently infiltrated with carbon. The resulting fibers had the compositions shown in Tables 2 and 3 below. Half cells were prepared for several batches of fibers, and the FCE, 5-cycle coulombic efficiency (5CE), 1 SDC, and tenth cycle coulombic efficiency (10CE) were determined. The results are summarized in Table 4 below.

[0061] Table 2

[0062]

[0063]

[0064]

[0065] Table 3

[0066]

[0067]

[0068]

[0069] Table 4

[0070]

[0071]

[0072]

[0073] Blank cells in Tables 2-4 represent properties that were not measured and / or undetectable.

[0074] As shown above, by maintaining the desired silicon content, crystallite size and carbon content, Examples 1-27 each achieve a FCE of at least 78% and a 1SDC of at least 1300 mAh / g. In contrast, Comparative Examples 1 and 2 have very large crystallites and provide FCEs of 75.8% and 62.1%, respectively, and 1SDCs of 1162 and 1057 mAh / g, respectively. Comparative Example 3 has a low silicon content and a poor 1SDC. Comparative Examples 4 and 5 have very high carbon contents and insufficient 1SDC. Comparative Examples 6 and 7 have good 1SDC, but low carbon contents result in poor FCE. Comparative Examples 8-18 have small crystallites and / or high carbon contents, and the resulting 1SDC and / or FCE are insufficient. Comparative Examples 19-32 each have a silicon crystallite size below 10 nm and only achieve a FCE of up to 65.5%. Figure 1 The effect of silicon crystallite size on 1SDC is shown. Figure 2 The effects of silicon content and silicon crystallite size in the composite fibers on 10CE are shown.

[0075] Example 2: Thermal Effects on Crystallite Size

[0076] Table 5 below summarizes the reduction conditions for selected PSFT from Table 2 above. To form PSFT, a mixture of silica fibers, Mg and a moderator (sodium chloride, alumina beads and / or flaky alumina) is loaded into a reactor. In particular, Comparative Examples 1-3 use an alumina crucible, Comparative Examples 4, 5, 10-20 and 26-30 and Examples 6, 7, 9, 11, 22 and 26 use a metal crucible, and the remaining examples use a rotary kiln. The reactions were carried out in an argon atmosphere, and the fibers were washed before analysis (analysis results are in Table 2). As shown, by controlling the reaction conditions, such as the ratio of moderator to magnesium, the crystallite size can be adjusted to fall within the range disclosed herein. Selected examples are plotted at Figure 3 to demonstrate the effect of ΔT on the size of silicon crystallites.

[0077] Table 5

[0078]

[0079]

[0080]

[0081]

[0082] Although various embodiments have been shown and described, the present disclosure is not limited to such embodiments, and will be understood to include all modifications and variations as will be apparent to those of ordinary skill in the art. Therefore, it should be understood that the present disclosure is not intended to be limited to the particular forms disclosed; on the contrary, the present invention covers all modifications, equivalents and substitutes that fall within the spirit and scope of the present disclosure as defined by the appended claims.

Claims

1. A composite fiber comprising: a porous silicon phase comprising elemental silicon; a porous carbon phase comprising elemental carbon; wherein the silicon phase and the carbon phase form an entangled network structure in the composite fiber, so that each of the silicon phase and the carbon phase is interconnected and continuous throughout the composite fiber; wherein the silicon phase comprises at least 75% by weight of elemental silicon in the form of silicon crystallites having an average size of 15 to 50 nm; wherein the carbon phase accounts for 20 to 60 weight percent of the composite fiber; and wherein the silicon phase and the carbon phase together constitute at least 50 weight % of the composite fiber.

2. The composite fiber according to claim 1, wherein the composite fiber has a thickness of 0.1 to 45 μm. 2 / g and a BET specific surface area greater than 0 to 0.25 cm 3 / g pore volume. The composite fiber according to claim 1 , wherein the composite fiber has an average pore diameter of 5 to 80 nm.

4. The composite fiber of claim 1, wherein the composite fiber has an aspect ratio of fiber length to diameter of at least 3.

5. The composite fiber of claim 1, wherein the silicon phase and the carbon phase together constitute at least 90% by weight of the composite fiber.

6. The composite fiber of claim 5, wherein the silicon phase comprises at least 90 weight percent elemental silicon, the silicon crystallites have an average size of 20 to 40 nm, and the carbon phase comprises 20 to 45 weight percent of the composite fiber.

7. The composite fiber of claim 5, wherein the silicon phase comprises 75 to 90 weight percent elemental silicon, the silicon crystallites have an average size of 20 to 45 nm, and the carbon phase comprises 32 to 50 weight percent of the composite fiber.

8. A method for producing the composite fiber according to claim 1, comprising: forming a porous fiber template comprising one of carbon or silicon, wherein the porous fiber template comprises one of the silicon phase or the carbon phase; as well as The porous fiber template is infiltrated with the other of carbon or silicon to form an infiltrating phase, wherein the infiltrating phase comprises the other of the silicon phase or the carbon phase.

9. The method of claim 8, wherein the porous fiber template consists essentially of carbon.

10. The method of claim 8, wherein the porous fiber template consists essentially of silicon.

11. The method of claim 8, wherein the average pore size of the permeating phase is 0.1 to 5 nm smaller than the average pore size of the porous fiber template.

12. The method of claim 11, wherein infiltrating the porous fiber template comprises chemical vapor deposition, physical vapor deposition, sputtering, atomic layer deposition, or pyrolysis.

13. The method of claim 11, wherein the porous fiber template comprises silicon, and forming the porous fiber template comprises: heating the silica precursor fibers to a temperature of about 550°C to about 600°C in the presence of magnesium and a moderator, wherein the moderator is present in an amount sufficient to achieve a maximum reaction temperature of at least 300°C; and The weight ratio of the moderator to the magnesium is less than 15.

14. The method of claim 13, wherein the moderator comprises sodium chloride and the maximum temperature is maintained below 900°C.

15. The method of claim 8, further comprising reacting the composite fiber with a lithium source to form Li x Si alloy, wherein x is greater than 0 to 4. 16 . An electrode active material comprising the composite fiber according to claim 1 .

17. An electrode comprising the electrode active material of claim 16, wherein the electrode has a first coulombic efficiency of at least 78% and a first cycle specific delithiation capacity of at least 1300 mAh / g.

18. The electrode of claim 17, wherein the silicon phase comprises at least 90% by weight elemental silicon, the silicon crystallites have an average size of 20 to 40 nm, and the carbon phase comprises 20 to 45% by weight of the composite fibers; and The electrode has a first cycle specific delithiation capacity of at least 1800 mAh / g.

19. The electrode of claim 17, wherein the silicon phase comprises 75 to 90 weight percent elemental silicon, the silicon crystallites have an average size of 20 to 45 nm, and the carbon phase comprises 32 to 50 weight percent of the composite fibers; and The electrode has a tenth cycle Coulombic efficiency greater than 98.7%.

20. A battery comprising the electrode of claim 16.